Penyelesaian Sengketa Perbatasan Darat di Segmen Bidjael Sunan Oben antara Indonesia dan Timor Leste - Sudika Mangku, Dewa Gede (Universitas Negeri Malang, 2020)
This study aims to analyze the settlement of land border disputes in the Sunan-Oben Bidjael Segment between Indonesia and Timor Leste based on international law. This research is a normative study that uses a statutory editor. The results of this study indicate that both Indonesia and Timor Leste have formed a Joint Border Committee as a forum for resolving land boundary disputes which was then continued to form the Technical Sub-Committee on Border Demarcation and Regulation (TSC - BDR) which has agreed to use the Convention for the Demarcation of Portuguese and Dutch Dominions on the Island of Timor 1904 (Treaty 1904) and Permanent Court of Arbitration 1914 (PCA 1914) as the legal basis for determining and confirming land boundaries between Indonesia and Timor Leste. Based on the 2005 Provisional Agreement Article 6 point (b), which implies that local communities, in this case, indigenous peoples / traditional leaders at the borders are given space to be involved in the dispute resolution process that occurs on the border of the two countries by promoting peaceful and non-violent methods in accordance with Article 8 Provisional Agreement 2005. Whereas the people who inhabit West Timor (Indonesia) and the people who live in East Timor (Timor Leste) have the same socio-cultural background, so it can be ascertained that the customary law system that applies in these two groups of people the same. The substance of the customary law can regulate land issues, as well as the boundaries of customary territories, the potential for customary leaders to actually play a negotiating role to resolve these problems.